2018
DOI: 10.3390/f9040203
|View full text |Cite
|
Sign up to set email alerts
|

Phytophthora cinnamomi Colonized Reclaimed Surface Mined Sites in Eastern Kentucky: Implications for the Restoration of Susceptible Species

Abstract: Appalachian forests are threatened by a number of factors, especially introduced pests and pathogens. Among these is Phytophthora cinnamomi, a soil-borne oomycete pathogen known to cause root rot in American chestnut, shortleaf pine, and other native tree species. This study was initiated to characterize the incidence of P. cinnamomi on surface mined lands in eastern Kentucky, USA, representing a range of time since reclamation (10, 12, 15, and 20 years since reclamation). Incidence of P. cinnamomi was correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…Similarly, estimated aboveground OC storage (25-66 Mg/ha) at the 19-year-old site was consistent with 48.9 Mg/ha tree OC reported by Avera et al [25] at a 21-year-old site in western Virginia. Taken together, with the 17.3 Mg/ha of OC stored in soils in white oak plots (see [32]), these data demonstrate total ecosystem OC (conservatively estimated) exceeding 43 Mg/ha in white oak plots, and likely much higher in white pine and yellow poplar plots, contributing to the literature demonstrating the significant OC storage potential of surface-mined sites.…”
Section: Carbonsupporting
confidence: 62%
See 1 more Smart Citation
“…Similarly, estimated aboveground OC storage (25-66 Mg/ha) at the 19-year-old site was consistent with 48.9 Mg/ha tree OC reported by Avera et al [25] at a 21-year-old site in western Virginia. Taken together, with the 17.3 Mg/ha of OC stored in soils in white oak plots (see [32]), these data demonstrate total ecosystem OC (conservatively estimated) exceeding 43 Mg/ha in white oak plots, and likely much higher in white pine and yellow poplar plots, contributing to the literature demonstrating the significant OC storage potential of surface-mined sites.…”
Section: Carbonsupporting
confidence: 62%
“…Alongside OC accumulation in soils, tree biomass at the 19-year-old site demonstrated significant OC storage, with total OC storage in tree biomass estimated at 25.8 Mg/ha (White Oak), 66.1 Mg/ha (White Pine), and 42.8 Mg/ha (Yellow Poplar), and annual OC sequestration rates ranging from 1.44 to 3.67 Mg/ha/yr (Table 3). [32]. Tree biomass data reflect 18 growing seasons after reclamation.…”
Section: Carbonmentioning
confidence: 99%
“…A further example is that of young sessile oak Quercus petraea seedlings grown by commercial nurseries; seeds collected from an ecologically sensitive site in Scotland and destined for translocation back to that site, once grown, were found to harbor the root pathogen Phytophthora quercina (Green et al 2020). Gyeltshen et al (2021) suggests that in Australia nurseries supplying seedlings for restoration sites should screen their plants for the presence of Phytophthora cinnamomi which has driven extensive declines of native vegetation in forest ecosystems and is limiting the species that can be established during ecological restoration (Sena et al 2018a(Sena et al , 2018b.…”
Section: Introductionmentioning
confidence: 99%
“…However, elimination of any soil borne pathogen is dependent on its survival ability and the environmental conditions. There have been many studies on P. cinnamomi, often based on temperature alone, and often under laboratory or glasshouse conditions (see review [18]). Burgess et al [19] and [20] have reported field survival and ability to cause disease at temperatures <6 • C, while Gallo et al [21] demonstrated inactivation of the pathogen in dry soils at 38 • C after 2 h, with 2 h at 40 or 42 • C killing all propagules.…”
Section: Introductionmentioning
confidence: 99%